Conversational narrative : storytelling in everyday talk - Norrick, Neal R. (Amsterdam studies in the theory and history of linguistic science. Current issues in linguistic theory, 2000)
This book investigates the forms and functions of storytelling in everyday conversation. It develops a rhetoric of everyday storytelling through an integrated approach to both the internal structure and the contextual integration of narrative passages. It aims at a more complete picture of oral narrative through analysis of a wider range of natural data, including personal anecdotes told for humor, put-down stories told for self-aggrandizement, family stories retold to ratify membership and so on, as well as marginal stories and narrative-like passages to delineate the boundaries of conversati.